(untitled) (International Journal of Engineering and Computer Science, 2015)
In today’s scenario, web search plays an important role for various search services over the internet. So to provide best result of searches, in the proposed model we suggest three modes of the ranking process. This will be done based on three processes 1. User query based Advertisement 2. Time Stamp based Analysis 3. Domain based search. In the first process when the user searches the query the related advertisement will be displayed on the web browser by eliminating the unwanted advertisements and hence makes the view of the web pages more optimized and completely useful for the users. In the second process we trace the session i.e. time stamp of a particular user hence by using the time stamp the page which has the maximum amount of time in second will be ranked as first. In the third process based on the particular search query it displays the forum based on the domain given as option when they search. Before entering the search the user can opt for the domain of his/her interest and finely refine the search results to their interest. This proposed model is implemented by applying Stemming Algorithm and Time stamp.